A Presença De Alcalóides Em Espécies Botânicas Da Amazônia - Menispermaceae - Rocha, Arnaldo F.I. da; Luz, Arnaldo Iran R.; Silva, Marlene Freitas da (Acta Amazonica, 1984)
A list of, Menispermaceae species from the Instituto Nacional de Pesquisas da Amazônia herbarium is, presented with the. respective results of the indicative test of the presence or not of alkaloids. An avaliation of the chemical-alkaloidical characteristics of, this family are also discussed, with emphasis on Amazonian genera.